2019
DOI: 10.1088/1361-6528/ab414e
|View full text |Cite
|
Sign up to set email alerts
|

High-performance humidity sensor using Schottky-contacted SnS nanoflakes for noncontact healthcare monitoring

Abstract: Humidity sensors based on flexible sensitive nanomaterials are very attractive in noncontact healthcare monitoring. However, the existing humidity sensors have some shortcomings such as limited sensitivity, narrow relative humidity (RH) range, and a complex process. Herein, we show that a tin sulphide (SnS) nanoflakes-based sensor presents high humidity sensing behaviour both in rigid and flexible substrate. The sensing mechanism based on the Schottky nature of a SnS-metal contact endows the asfabricated senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…High humidity sensing response of GQDs/AgNPs over pristine GQDs and pristine AgNPs may be attributed to two main aspects: (i) formation of Schottky junctions at the metal–semiconductor interfaces that play a crucial role for charge transfer enhancements [ 53 , 54 ]. Energy band diagrams of GQDs and AgNPs before contact are displayed in figure 6 c .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High humidity sensing response of GQDs/AgNPs over pristine GQDs and pristine AgNPs may be attributed to two main aspects: (i) formation of Schottky junctions at the metal–semiconductor interfaces that play a crucial role for charge transfer enhancements [ 53 , 54 ]. Energy band diagrams of GQDs and AgNPs before contact are displayed in figure 6 c .…”
Section: Resultsmentioning
confidence: 99%
“…When GQD are well embedded on AgNPs, the electrons can be transferred between two sensing nanomaterials to equilibrate the Fermi energy level. The band bending occurs and forms Schottky barrier [ 53 , 54 ] ( figure 6 d ). At low RH level (25% RH), Schottky barrier ( ɸ B ) exhibits a high value based on the Schottky junction formation with intrinsic conductions of metal–semiconductor nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wearable electronic textile humidity sensors based on carbon nanotubes and composite fibers have also been developed [14,15]. The Schottky structure has been used extensively in photoelectric sensing, and Schottky structure humidity sensors for noncontact medical monitoring have been reported in recent years [16]. Inspired by the excellent performance of graphene and metal oxide, SiNW/ZnO/rGO and SiNW/TiO 2 /rGO Schottky composite metal nanomaterials were developed and used for sensitive detection of trace explosive vapors [17,18], and we found that their response to humidity is very sensitive and that they can be used for human respiration monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Its direct bandgap energy is a desirable ~ 1.3 eV with an indirect bandgap near 1.1 eV 6 , 7 and a high optical absorption coefficient 8 . Also, SnS-based materials have interesting properties, leading to applications such as high-performance humidity sensors 9 , ion batteries 10 , thermoelectric devices 11 , exciton-driven chemical sensors 12 , and Schottky barrier diodes 13 . They also exhibit valley-selective linear dichroism 14 .…”
Section: Introductionmentioning
confidence: 99%